2000
DOI: 10.1149/1.1394046
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Effect of Platinum on Oxygen Reduction An Ab Initio Model Including Electrode Potential Dependence

Abstract: The effects of bonding to a platinum atom are calculated for the reduction of oxygen to water. The electron-correlation corrected MP2 method is used, and the electrode potential is modeled by variations in values for the electron affinities of the reaction centers. Potential-dependent transition state structures and activation energies are reported for the one-electron reactions Pt-O 2 ϩ H ϩ (aq) ϩ e Ϫ (U) r Pt-OOH [i ] Pt-OOH ϩ H ϩ (aq) ϩ e Ϫ (U) r Pt-(OHOH) [ii] Pt-(OHOH) ϩ H ϩ (aq) ϩ e Ϫ (U) r Pt-OH ϩ H 2 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
219
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(232 citation statements)
references
References 38 publications
11
219
1
1
Order By: Relevance
“…3 This activated HOO* species decomposes to adsorbed O* and HO* species with its activation barrier small (i.e., 0.06 eV) according to previous DFT studies. 3,24 The reduction of HOO* may lead to H 2 O by the formation of hydrogen peroxide (H 2 O 2 *) intermediate (i.e., a series pathway) 3,21,55 or by directly forming H 2 O and adsorbed O*. 2,3,55 Although the former was suggested to be the lower energy pathway, 55 it has generally been accepted that the H 2 O 2 * intermediate is unstable and thus readily dissociates homolytically into HO* + HO* species.…”
Section: Resultsmentioning
confidence: 99%
“…3 This activated HOO* species decomposes to adsorbed O* and HO* species with its activation barrier small (i.e., 0.06 eV) according to previous DFT studies. 3,24 The reduction of HOO* may lead to H 2 O by the formation of hydrogen peroxide (H 2 O 2 *) intermediate (i.e., a series pathway) 3,21,55 or by directly forming H 2 O and adsorbed O*. 2,3,55 Although the former was suggested to be the lower energy pathway, 55 it has generally been accepted that the H 2 O 2 * intermediate is unstable and thus readily dissociates homolytically into HO* + HO* species.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretically, it has been shown that bonding of O 2 , OOH* and H 2 O 2 to Pt surfaces decreases the high activation energies for these outer-sphere reductions [63][64][65], but at the same time increases HO* activation energy [63] and stabilises OH ads and O ads [12,13,[66][67][68][69][70]. Because of that, the formation of OOH ads , compared to O ads + OH ads , would not be stable [67], and so, the reduction of this species, if formed, would occur in the solution side of the interface.…”
Section: Role Of Oh Ads /O Ads In the Orr Dynamics On Pt(111)mentioning
confidence: 99%
“…These studies supplied information on each elementary step, such as activation energies, reaction energies, and reversible potentials. Anderson and co-workers [54,55] investigated the activation barrier for each of the following electron transfer steps:…”
Section: Oxygen Reduction Reactionmentioning
confidence: 99%